In Silico ADMET Evaluation of Natural DPP-IV Inhibitors for Rational Drug Design against Diabetes - Singla, Rajeev K.; Shen, Bairong (Current Drug Metabolism, 2020)
Background: As a metabolic and lifestyle disorder, diabetes mellitus poses a prodigious health risk. Out of the many key targets, DPP-IV is one of the very imperative therapeutic targets for the treatment of diabetic patients. Methods: In our current study, we have done the in silico simulations of ADME-T properties for naturally originated potent DPP-IV inhibitors like quinovic acid, stigmasterol, quinovic acid-3-beta-D-glycopyranoside, zygophyloside E, and lupeol. Structural topographies associated with different pharmacokinetic properties have been systematically assessed. Results: Glycosylation on quinovic acid is found to be noteworthy for the improvement of pharmacokinetic and toxicological properties, which leads to the prediction that zygophyloside E can be further tailored down to get the lead DPP-IV inhibitor. Conclusion: This assessment provides useful insight into the future development of novel drugs for the treatment of diabetes mellitus.
Keywords: Dipeptidyl peptidase 4